Immunolocalization of Leptin and its Receptor (ObR-b) in Equine Placenta at Term and Plasma Level Measurement in the Late Gestation - Pazinato, Fernanda Maria; Curcio, Bruna da Rosa; Varela Junior, Antonio Sergio; Corcini, Carine Dahl; Wendt, Camila Gervini; Moreira, Fabiana; Schmit, Rubia Alves [UNESP]; Wayne Nogueira, Carlos Eduardo (Elsevier B.V., 2019)
Placental tissues from humans, rodents, and farm animal contain leptin and its receptor. Expression of leptin has already been described in horses, although there is no description about immunolocalization of leptin and its receptor. The aim of the present study was to investigate the presence and distribution of leptin and ObR-b in the equine placenta at term by immunofluorescence staining, and the changes on plasma leptin concentrations during late gestation. The present study involved eight Criollo-type mares carrying healthy pregnancies. Blood samples were collected during the third trimester of gestation, at foaling, and at 24 hours after foaling. Leptin concentrations were analyzed via radioimmunoassay. Plasma leptin concentrations did not change from the 8th to the 10th month of gestation and displayed a discrete decrease 24 hours after parturition (P=.07). The expression of leptin and ObR-b was observed in the cytoplasm of pseudostratified epithelial cells in the areolar region and in the epithelium of micro-cotyledons. Also, leptin receptor was allocated in the apical surface of the cells. The presence of leptin and its receptor (ObR-b) in the placenta of mares at term supports an endocrine and autocrine/paracrine action of leptin within this organ. (C) 2019 Published by Elsevier Inc.
Keywords: Mares; Immunofluorescence; Autocrine action; Placental metabolism